Az uralkodói hatalom korlátai az ókeresztény szerzők műveiben - Sáry, Pál (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Christians have never considered the power of the ruler to be unlimited. According to Christian views formulated in antiquity, the emperor was obliged to observe revealed divine laws, the rules of natural law, the positive laws of the state, and the rules of canon law. According to the Christian view, which coincides with the Jewish position, the ruler could not claim to be worshipped as a god by his subjects. Christians also adopted the doctrines of natural law from Greco-Roman philosophy, according to which the ruler was obliged to judge fairly and make just laws. Apologists (especially Tertullian) proclaimed that nature grants everyone the right to freely choose their religion, and therefore the emperor should not use religious coercion. According to the rules of natural law, the ruler was obliged to respect the property rights of his subjects. The emperor had to adhere to the rules of justice even in war. Although according to Roman law, the emperor was not bound by the rules of positive law, Christians also expected a good emperor to comply with state laws. In addition to all this, the Catholic bishops required the Christian emperors to adhere to the rules of canon law: if they committed a sin, they should follow the provisions of penitential discipline; they should not interfere in the internal affairs of the Church, not imagine themselves to be high priests, not define theological doctrines; in other words, they should respect the rules of competence defined by the Church.